Influence of organic manures and biofertilizers on the yield of Amaranthus dubius - Abhilash, ES; Aswathi, AS; Parayil, Sheeja P (Asia Pacific Journal of Environment Ecology and Sustainable Development, 2014)
The maximum productivity was shown by vermicompost (T1) treated plants. The next higher productivity was exhibited by Pseudomonas treated plants (T2). After 30 th day vermicompost treated plants had higher growth rate compared to pseudomonas treated plants. The leaves of vermicompost treated plants are large and more greenish in colour. The stem is more swollen and hard. Pseudomonas also showed comparatively greater vegetative growth to Amaranth plants. DOI: http://dx.doi.org/10.3126/apjeesd.v1i1.9507 Asia Pacific Journal of Environment Ecology and Sustainable Development 2013; 1: 26-28